2021
DOI: 10.1177/14550725211050765
|View full text |Cite
|
Sign up to set email alerts
|

Former inpatients’ narratives of substance use four years after substance use disorder treatment: A qualitative follow-up study

Abstract: Aim: The aim of this study was to explore the narratives of former substance use disorder (SUD) inpatients about substance use after their discharge from long-term SUD treatment in 2017. Method: We conducted semi-structured in-depth interviews with 11 former inpatients of SUD treatment. The data were analysed using a qualitative, thematic analysis model. Findings: During the analysis, two main themes emerged pertaining to participant reflections on substance use – their experience of non-problematic substance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Parental separation was related more strongly to alcohol use among adolescents The authors emphasise that interventions and policies should address social, developmental, and psychological factors. Hystad and Wangensteen (2022) explored the narratives of former substance use disorder (SUD) inpatients after their discharge from longterm SUD treatment. Most of the participants continued to use substances in some way, and some reported that such use did not affect them negatively.…”
Section: Two New Titlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental separation was related more strongly to alcohol use among adolescents The authors emphasise that interventions and policies should address social, developmental, and psychological factors. Hystad and Wangensteen (2022) explored the narratives of former substance use disorder (SUD) inpatients after their discharge from longterm SUD treatment. Most of the participants continued to use substances in some way, and some reported that such use did not affect them negatively.…”
Section: Two New Titlesmentioning
confidence: 99%
“…Hystad and Wangensteen (2022) explored the narratives of former substance use disorder (SUD) inpatients after their discharge from long-term SUD treatment. Most of the participants continued to use substances in some way, and some reported that such use did not affect them negatively.…”
Section: In This Issuementioning
confidence: 99%
“…Sobriety may then counter such threats. However, former SUD patients may live a good life while continuing to use substances ( Hystad and Vangensteen, 2022 ), and previous findings ( Laudet, 2007 ) indicate that although sobriety may be a dichotomous foundation, it need not be inconsistent with recovery regarded as more continuous in nature. Indeed, recovery from SUD (or other disorders) may be understood to be a process, but also a vision, a philosophy or attitude, and a set of outcomes ( Silverstein and Bellack, 2008 ).…”
mentioning
confidence: 99%
“…In SUD, compulsive use of substances continues despite severe negative consequences for mental and physical health, education and work, relationships with family and friends, economic security, and participation in society ( Duncan, 2020 ; WHO, 2015 ). For most people with SUD, substance use temporarily helps them feel better about and able to cope with, for example, trauma and adverse childhood experiences, attention deficit hyperactivity disorder (ADHD), anxiety, depression, challenging emotions, family demands, loneliness, and dire living conditions ( Felitti & Anda, 2010 ; Gil-Rivas & McWhorter, 2013 ; Kassel et al, 2013 ; Topor et al, 2021 ). Frequent use of substances may lead to a worse life situation, with substances causing more problems than they solve.…”
mentioning
confidence: 99%